Prarancangan dan Analisis Finansial Unit Biodigester Tipe Fixed Dome untuk Pengolahan Sampah Organik Pasar Cikurubuk Kota Tasikmalaya - Mellyanawaty, Melly; Hermawan, Riki; Nofiyanti, Estin (Universitas Tanjungpura, 2026)
Organic waste is the dominant component of daily market refuse and has substantial potential to be converted into renewable energy. This study analyzes the characteristics of organic waste at Cikurubuk Market in Tasikmalaya and proposes a 335 m³ fixed-dome biodigester as a treatment and energy-recovery solution. The organic waste stream, reaching 3,276.09 kg/day, can generate approximately 61.39 m³ of methane per day. The economic assessment indicates that electricity generation offers the most favorable outcome, yielding Rp 94.9 million annually, with a benefit–cost ratio of 2.27 and a payback period of about 16 years. Environmentally, the biodigester can substantially reduce the amount of organic waste sent to landfills and lower methane emissions from open decomposition, while producing digestate suitable for use as organic fertilizer. These results demonstrate that community-scale biodigesters represent an effective, sustainable, and economically viable option for managing market waste and supplying renewable energy in urban areas.